1982
DOI: 10.1007/bf02534587
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and phospholipid composition ofBacillus megaterium spores with altered germination properties

Abstract: The ability of spores to trigger germination was altered by growing spores at either a suboptimal temperature or in a rich medium modified by substituting L-isoleucine for D-glucose. Compared to the control, spores grown in the presence of isoleucine germinated more readily between 20 and 28 C, while spores grown at 20 C germinated slower than the control at any temperature tested. Analysis of the composition of these spores indicated that spores grown in the presence of isoleucine had much higher levels of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We tried to determine the distribution of 45Ca in the spore preparations by counting the radioactivity of the fractions obtained after disruption of the spores, but we failed to do so because too little activity was recovered from any fraction. As candidates for the "site," the cortex and the inner membrane were suggested for the following reasons : first, we used decoated spores; second, we found that there was an interaction of cortex peptidoglycans with cations (10) ; third, Vary and coworkers (16,23,24) had suggested the inner membrane as the site reactive with the germinant. Therefore, binding of calcium to the isolated cortex and inner membrane preparations, the latter of which might be contaminated with the outer membrane and the cortex fragments, was examined to obtain possible evidence for the location of the calcium-reacting site.…”
Section: Germination Properties Of Cation-exchanged Spores Of Mae-05mentioning
confidence: 99%
See 1 more Smart Citation
“…We tried to determine the distribution of 45Ca in the spore preparations by counting the radioactivity of the fractions obtained after disruption of the spores, but we failed to do so because too little activity was recovered from any fraction. As candidates for the "site," the cortex and the inner membrane were suggested for the following reasons : first, we used decoated spores; second, we found that there was an interaction of cortex peptidoglycans with cations (10) ; third, Vary and coworkers (16,23,24) had suggested the inner membrane as the site reactive with the germinant. Therefore, binding of calcium to the isolated cortex and inner membrane preparations, the latter of which might be contaminated with the outer membrane and the cortex fragments, was examined to obtain possible evidence for the location of the calcium-reacting site.…”
Section: Germination Properties Of Cation-exchanged Spores Of Mae-05mentioning
confidence: 99%
“…We propose that a change in permeability of the inner membrane to DPA and cations is an important event in the initiation of germination because release of DPA and cations, loss of heat resistance and collapse of cortex expansion occurred at almost the same time (10). Vary and his co-worders (16,23,24) suggested, from the observation that anisotropy of the inner membrane changed in the presence of germinants, that in the inner membrane there is a substance which could change its conformation upon contact with germinants. It is still unclear how calcium interacts with the membrane consisting of proteins (enzymes), phospholipids, cytochromes, carotenoids and other substances (17), although we propose that the calcium may contribute to a change in permeability and conformation of the membrane caused by germinants.…”
Section: Germination Properties Of Cation-exchanged Spores Of Mae-05mentioning
confidence: 99%
“…Lipid extraction. To investigate the lipids, we mechanically disrupted the B. megaterium spores and extracted the lipids by method A of Bligh and Dyer, which has been routinely used (2,4,7,15) for analysis of bacillus lipids. Only 68% of the total spore fatty acids were in the organic phase of the lipid extract (Table 1), and the remainder was distributed in other fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Change in membrane structure has been reported to affect germination properties of B. megaterium spores (35).…”
Section: Discussionmentioning
confidence: 99%